Public Health Personnel’s Performance: the Role of Perceived Organizational Support and Work Engagement - Ranihusna, Desti; Ulfa, Unzilla Ainun; Wartini, Sri (JDM (Jurnal Dinamika Manajemen), 2021)
Organizational support and work engagement are important for public health personnel at Balai Kesehatan Masyarakat to feel comfortable and safe at the workplace. Patient visits data assessed and evaluated by Dinas Kesehatan Central Java Province shows that the average patient visits within the last five years in several working areas at Balai Kesehatan Masyarakat Central Java Province significantly decrease. The purpose of the research is to examine public health personnel’s performance through perceived organizational support and work engagement. This research used a quantitative research method and questionnaires distributed to 86 public health personnel in Balai Kesehatan Masyarakat that were tested using SEM-PLS with smart pls 3.0 program. The findings show that perceived organizational support and work engagement significantly affect performance; thus, all of the hypothesis is acceptable.